PERBANKAN PERSPEKTIF HADIS MAUDHU'IY (Mazahib, 2012)
The hadith that talks about the bank in this study according to the results there takhrij narrated by al-Bukhahri so did Abu Dawud, and the results of research that has been made known that the hadith is authentic quality. Hadith of the banks in this study refers to the concept of Islamic Banking. From here then understood that the modus operandi of the Sharia Bank regardless of usury, because the basic principle of operation is the same kerjasa capital called al-syarikah, and the capital is used to try, then the benefits for the results, "sharing" between the parties banks and customers. Therefore, every Muslim should just make a deal, save money, deposit, and use of existing services to banking institutions, especially in Islamic banks.